Implementasi Program Angkutan Siswa Trans Serasi Dalam Meningkatkan Pelayanan Angkutan Siswa Gratis di Kabupaten Tabanan - Wira Utami, Dewa Ayu Dwi (Jurnal Nawala Politika, 2017)
O ne form of public service needed by the public is public transport services. But this time, in Tabanan regency that public transportation tends to be abandoned by the public due to the low level of service provided by the government. Seeing the condition of urban transport services is decrease, affecting students who prefer to use motorcycles when they go to school instead of using urban transport. The increasing number of students who ride motorcycles cause higher number of traffic violations and accident rates. Responding to the phenomenon, the Department of Transportation Tabanan District providing free school transportation called Trans Serasi which target the school students, especially junior high school students in Tabanan regency. This research was conducted using descriptive qualitative data collection techniques such as in-depth interviews. The indicators used to discuss the results of the research is (1) communication indicators, (2) resource indicators, (3) disposition indicators, and (4) indicators of bureaucratic structures which is used to view the Implementation of Trans Serasi Transportation Program in Tabanan District. The results of this study indicate Trans Serasi in Tabanan regency is still not running optimally. It is seen from the four indicators that only communications indicators that have been implemented properly, while the indicators of resources, dispositions, and bureaucratic structures are still not running maximally   K eywords : Implementation, Service, Transportation of Trans-Serasi Student